2013
DOI: 10.1093/nar/gkt156
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β–specific recruitment of GCN5 histone acetyltransferase induces the release of PAF1 from chromatin for the de-repression of inflammatory response genes

Abstract: To determine the functional specificity of inflammation, it is critical to orchestrate the timely activation and repression of inflammatory responses. Here, we explored the PAF1 (RNA polymerase II associated factor)-mediated signal- and locus-specific repression of genes induced through the pro-inflammatory cytokine interleukin (IL)-1β. Using microarray analysis, we identified the PAF1 target genes whose expression was further enhanced by PAF1 knockdown in IL-1β–stimulated HepG2 hepatocarcinomas. PAF1 bound ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Nuclear factor-κB (NF-κB) cooperates with GCN5/PCAF complex to regulate the expression of multiple genes (4446), and NF-κB also serves as a regulator of NKG2D ligands (47). Hence, it is possible that inflammatory cytokines activate NF-κB, which in turn recruits GCN5/PCAF to upregulate NKG2D ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor-κB (NF-κB) cooperates with GCN5/PCAF complex to regulate the expression of multiple genes (4446), and NF-κB also serves as a regulator of NKG2D ligands (47). Hence, it is possible that inflammatory cytokines activate NF-κB, which in turn recruits GCN5/PCAF to upregulate NKG2D ligands.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually found associated with the coding regions of the actively transcribing genes (40,41) and hence suggested as an activator of transcription. However, there are also a handful of reports proposing a negative role of PAFc in transcription (42)(43)(44)(45)(46). Both Paf1 and Ctr9 repress the SER3 gene by reducing nucleosome occupancy and recruiting of Spt16 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin IP was performed as described previously with some modifications 25 . Briefly, 4 Â 10 7 cells were cross-linked with 1% formaldehyde and lysed in cell lysis buffer (20 mM Tris-HCl, pH 8.0, 85 mM KCl, 0.5% NP-40, with protease inhibitors).…”
Section: Methodsmentioning
confidence: 99%
“…To understand how p53 levels were increased in hCdc73-deficient cells, we first examined whether hCdc73 repressed the transcription of p53, because it has been reported that PAFc represses immediate early genes and interleukin-1-inducible PLAU genes 25 . p53 gene transcription was active under basal conditions, and relatively strong RNA Pol II-Ser2P occupancy was detected at the coding region of the p53 locus in control cells (Fig.…”
mentioning
confidence: 99%